2010
DOI: 10.1182/blood-2010-04-279497
|View full text |Cite
|
Sign up to set email alerts
|

Vascular remodeling of the vitelline artery initiates extravascular emergence of hematopoietic clusters

Abstract: The vitelline artery is a temporary structure that undergoes extensive remodeling during midgestation to eventually become the superior mesenteric artery (also called the cranial mesenteric artery, in the mouse). Here we show that, during this remodeling process, large clusters of hematopoietic progenitors emerge via extravascular budding and form structures that resemble previously described mesenteric blood islands. We demonstrate through fate mapping of vascular endothelium that these mesenteric blood islan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 43 publications
3
61
1
1
Order By: Relevance
“…All IAHC cells express c-kit, but contaminating c-kit 1 cells are also present in the circulating blood and outside of the aorta. 2,15 To circumvent this issue, directlylabeled antibodies against c-kit were injected inside the aorta of nonfixed E10 embryos before AGM dissection/dissociation. Our procedure allows flushing out the blood from the aorta, staining all IAHCs, 10,16 and isolating IAHC cells only ( Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…All IAHC cells express c-kit, but contaminating c-kit 1 cells are also present in the circulating blood and outside of the aorta. 2,15 To circumvent this issue, directlylabeled antibodies against c-kit were injected inside the aorta of nonfixed E10 embryos before AGM dissection/dissociation. Our procedure allows flushing out the blood from the aorta, staining all IAHCs, 10,16 and isolating IAHC cells only ( Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…The LP origin of the DA has been further confirmed by lineage labelling using a HoxB6-Cre line, crossed with a Rosa26 reporter line, that uses the LP enhancer element of HoxB6 (Wasteson et al, 2008). Using this transgenic line, it has been demonstrated that all DA endothelial cells of the mid-gestation embryo and adult mouse derive from LP mesoderm (Wasteson et al, 2008;Zovein et al, 2010). Importantly, it was also determined that virtually the entire bone marrow haematopoietic system derives from the LP (Zovein et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…Using this transgenic line, it has been demonstrated that all DA endothelial cells of the mid-gestation embryo and adult mouse derive from LP mesoderm (Wasteson et al, 2008;Zovein et al, 2010). Importantly, it was also determined that virtually the entire bone marrow haematopoietic system derives from the LP (Zovein et al, 2010). However, neither the exact location of the DA mesodermal precursors in the LP nor their genetic programming is known.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated through fate mapping that the first HSCs arise as part of the hematopoietic progenitor clusters that emerge from the hemogenic endothelium and subendothelial layers at the ventral part of the dorsal aorta and in the vitelline artery (Rybtsov et al, 2011;Yokomizo et al, 2011). These small cell clusters of hematopoietic progenitors are closely associated with the endothelium and originate from vascular remodelling and extravascular budding (Boisset et al, 2010;Robin et al, 2011;Zovein et al, 2010). This involves changes in endothelial cell shape and loss of cellular adhesion that have been likened to the changes in cell adhesion that epithelial cells undergo during epithelial to mesenchymal transition (EMT).…”
Section: Introductionmentioning
confidence: 99%